X-ray detection with zinc-blende (cubic) GaN Schottky diodes - Gohil, T.; Whale, J.; Lioliou, G.; Novikov, Sergei V.; Foxon, C.T.; Kent, A.J.; Barnett, A.M. (Nature Publishing Group, 2016)
The room temperature X-ray responses as functions of time of two n type cubic GaN Schottky diodes (200 μm and 400 μm diameters) are reported. The current densities as functions of time for both diodes showed fast turn-on transients and increases in current density when illuminated with X-ray photons of energy up to 35 keV. The diodes were also electrically characterized: capacitance, implied depletion width and dark current measurements as functions of applied bias at room temperature are presented. At −5 V reverse bias, the capacitances of the diodes were measured to be (84.05 ± 0.01) pF and (121.67 ± 0.02) pF, respectively. At −5 V reverse bias, the dark current densities of the diodes were measured to be (347.2 ± 0.4) mA cm−2 and (189.0 ± 0.2) mA cm−2, respectively. The Schottky barrier heights of the devices (0.52 ± 0.07) eV and (0.63 ± 0.09) eV, respectively, were extracted from the forward dark current characteristics.